Steam reforming of olive oil mill wastewater with in situ hydrogen and carbon dioxide separation - Thermodynamic analysis - Cláudio Rocha (2017)
A thermodynamic analysis of the steam reforming reaction of olive oil mill wastewater (OMW) with in situ carbon dioxide (CO2) and hydrogen (H-2) simultaneous removal was performed. The idea behind is the integration of the reformer with a H-2-selective membrane and a CO2-sorbent in a hybrid multifunctional reactor. The simulations were performed at different temperatures (300-500 degrees C), pressures (11-1 bar), removal fractions of H-2 (0-0.8), removal fractions of CO2 (0-0.99) and also for different water contents in the feed (20-92 wt.%). The results were compared in terms of performance reached for the different reactor configurations: traditional reactor (TR), membrane reactor (MR) with H-2 separation, sorption-enhanced reactor (SER) with CO2 capture and sorption-enhanced membrane reactor (SEMR). For the SEMR, the optimum operation conditions were determined. An H-2 yield very close to the stoichiometric value of 13.54 was obtained at 1 bar, 500 degrees C, water content in the feed of 60-92 wt.% (steam-to-carbon feed ratio, SCFR = 2.1-16.0), fCO(2) = 0.99 and fH(2) = 0.80. The H-2 yield obtained in such optimum conditions corresponds to an enhancement of 141% comparatively to the TR. Moreover, under these operation conditions there is no significant production of CO2, CO, CH4 and coke.